Investigation of Chemical Composition, Antibacterial and Antioxidant Activity of Thymus daenensis and Thymus eriocalyx Essential Oils against Human Pathogenic Bacteria - mostafa alamholo (Pasteur Institute of Iran, 2020)
Introduction: Plant essential oils can be used as alternative agents for the treatment of antibiotic-resistant pathogenic bacteria. This study aimed to investigate the chemical composition, antibacterial, and antioxidant activity of Thymus eriocalyx and Thymus daenensis essential oils against Gram-positive and Gram-negative human pathogenic bacteria. Methods: The aerial part of Thymus eriocalyx and Thymus daenensis in the full flowering stage were collected from West Azerbaijan Province (Urmia), Iran, in 2014. We obtained the essential oils using a Clevenger device. The disc diffusion method was used to determine the antibacterial activity of the essential oils against 15 Gram-positive and Gram-negative PTCC and ATCC bacterial standards. Minimum inhibitory concentrations (MICs) and minimum bactericidal concentrations (MBCs) were measured by microdilution broth method in 96-well plate and free radical scavenging activity by 2,2-diphenyl-1-picrylhydrazyl. Chemical analysis of the essential oils performed out by gas chromatography connected to Mass spectrometry. Results: Eleven (94.06%) and seven (90.76%) compounds were identified in T. eriocalyx and T. daenensis essential oils, respectively. The major components of T. eriocalyx essential oil were thymol (37.8%) and α-terpineol (14.91%), and of T. daenensis were thymol (52.36%) and carvacrol (16.72%). T. eriocalyx essential oil showed the highest activity against B. cereus with MIC of 0.93 μg mL- and MBC of 1.87 μg mL-. The most potent radical scavenging activity was also obtained for T. daenensis essential oil. Conclusion:  Essential oil components of T. eriocalyx and T. daenensis may have the potential to be used as antimicrobial agents against antibiotic-resistant pathogenic bacteria.